Pro Visual C++/CLI and the .NET 2.0 Platform - R. G. Fraser, Stephen (Apress, 2012)
In the first edition of this book, I said .NET is the future. I need to correct that—C++/CLI is the future. Microsoft seems to have a set pattern when it comes to releasing their products. It takes them three versions to come out with a superior and polished product. Well, true to form, even though they call it .NET 2.0, this is version three and, to put it bluntly, Microsoft has hit the nail on the head once again.